Mechanisms and Control of NO2− Inhibition of Anaerobic Ammonium Oxidation (Anammox). (1st April 2017) - Li, Guangbin; Carvajal‐Arroyo, Jose Maria; Sierra‐Alvarez, Reyes; Field, Jim A.
Abstract : ABSTRACT: Nitrite (NO2 − ), one of the main substrates in the anaerobic ammonium oxidation (anammox) process, has the potential to inhibit anammox bacteria. The sensitivity of anammox cells with different energy status to NO2 − was evaluated, and addition of nitrate (NO3 − ) inhibition on the basis of narK gene with the putative function of facilitating NO3 − /NO2 − antiporter. The results showed that the resistance of anammox bacteria to NO2 − inhibition follows the order: active‐cells > starved‐cells > resting‐cells > starved‐/resting‐cells. Anammmox resting cells have increasing tolerance to NO2 − in the pH range from 7.0 to 7.5. Dissipating the proton gradient by using carbonyl cyanide m‐chlorophenyl hydrazine (CCCP) caused severe inhibition at all pH values including pH = 7.5. Addition of NO3 − enabled activity recovery of NO2 − ‐inhibited anammox bacteria regardless of whether the proton gradient was disrupted or not, supporting the hypothesis of NO3 − ‐dependent detoxification via a secondary transport system.